2022
DOI: 10.3390/vetsci9010032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Routine Management Procedures on the Welfare of Suckling Piglets

Abstract: Piglets often undergo several painful treatments during the initial days of their lives. In this review, we investigate the acute (i.e., immediate), short-, and long-term implications of piglet processing on behavioral, physiological, clinical, and performance parameters, and how welfare impairments depend on performance instead of sham procedure, alternative techniques, or the age of the piglets. Welfare indicators that have been used to determine the least distressing procedures and knowledge gaps with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
(374 reference statements)
0
2
0
Order By: Relevance
“…Castration is frequently performed by cutting the spermatic cords (Fredriksen et al, 2009) which can be performed using either a scalpel, an emasculator or scissors (Schmid et al 2022). While previous studies have observed no differences between tearing or cutting on the level of vocalisation (Tylor and Weary, 2000;Marchant-Forde et al, 2009), a recent study (Schmid et al, 2021) reported significant differences between cutting and tearing, indicating severe pain (measured in terms of vocalisation and body movement during the procedure) and increased tissue damage in piglets castrated with tearing.…”
Section: Surgical Castration 6251 Tools For Castrationmentioning
confidence: 99%
“…Castration is frequently performed by cutting the spermatic cords (Fredriksen et al, 2009) which can be performed using either a scalpel, an emasculator or scissors (Schmid et al 2022). While previous studies have observed no differences between tearing or cutting on the level of vocalisation (Tylor and Weary, 2000;Marchant-Forde et al, 2009), a recent study (Schmid et al, 2021) reported significant differences between cutting and tearing, indicating severe pain (measured in terms of vocalisation and body movement during the procedure) and increased tissue damage in piglets castrated with tearing.…”
Section: Surgical Castration 6251 Tools For Castrationmentioning
confidence: 99%
“…The developers of the PGS also theorized that exposure to livestock (animal experience) contributed to differences in scores (Viscardi and Turner, 2018), and this is supported by the difference in scores between public and industry respondents in the current study. While this suggests PGS may not be fully comparable between raters with different experience levels, the strong internal consistency means it can still be reliably used for training veterinary or industry professionals and sensitizing professionals and the public to pain in swine, helping to dispel persistent misconceptions (Steagall et al, 2021) and providing a rapid, simple and unobtrusive evaluation tool that can be more easily applied than behavioral or biomarker scales (Leach et al, 2012;Vitali et al, 2020;Schmid and Steinhoff-Wagner, 2022).…”
Section: Discussionmentioning
confidence: 99%